Biophysical characterisation of the Bcl-x pre-mRNA and binding specificity of the ellipticine derivative GQC-05: Implication for alternative splicing regulation - Bhogadia, Mohammed; Stone, Beth; Del Villar Guerra, Rafael; Muskett, Frederick W.; Ghosh, Sudipta; Taladriz-Sender, Andrea; Burley, Glenn A.; Eperon, Ian C.; Hudson, Andrew J.; Dominguez, Cyril (Frontiers in Molecular Biosciences, 2022)
The BCL2L1 gene expresses two isoforms of Bcl-x protein via the use of either of two alternative 5′ splice sites (5′ss) in exon 2. These proteins have antagonistic actions, Bcl-XL being anti-apoptotic and Bcl-XS pro-apoptotic. In a number of cancers the Bcl-XL isoform is over-expressed, resulting in cancer cell survival and growth, so switching splicing to the Xs isoform could have therapeutic benefits. We have previously proposed that a putative G-quadruplex (G4) exists downstream of the XS 5′ss and shown that the ellipticine derivative GQC-05, a previously identified DNA G4-specific ligand, induces an increase in the XS/XL ratio both in vitro and in cells. Here, we demonstrate that this G4 forms in vitro and that the structure is stabilised in the presence of GQC-05. We also show that GQC-05 binds RNA non-specifically in buffer conditions, but selectively to the Bcl-x G4 in the presence of nuclear extract, highlighting the limitations of biophysical measurements taken outside of a functional environment. We also demonstrate that GQC-05 is able to shift the equilibrium between competing G4 and duplex structures towards the G4 conformation, leading to an increase in accessibility of the XS 5′ss, supporting our previous model on the mechanism of action of GQC-05.